The relationship between spiritual health and resilience of nurses with their compassionate care in intensive care units - Mahnaz Rakhshan; Somaye Derakhshan; Majid Najafi Kalyani (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Nurses experience a demanding work environment, and the state of their spiritual health and resilience can impact their ability to provide compassionate care. The objective of this study was to examine the connection between spiritual health, resilience, and compassionate care among nurses working in intensive care units. MATERIALS AND METHODS: This descriptive cross-sectional study employed stratified sampling to select 340 nurses. The research utilized several instruments, including Demographic Information, Nurses' Compassionate Care, Iranian Muslim Adult Spiritual Health, and Connor and Davidson Resilience Questionnaires (significance level: 0.05). The data was analyzed by SPSS software version 24 using statistical tests including Chi-square, t-test, and Pearson's correlation coefficient. RESULTS: The results indicated that the majority of participants were female, with an average age of 32.65 years. The mean score for spiritual health was 192.53 ± 23.67, and the resilience score was 71.52 ± 13.43. The average score for compassionate care was 119.82 ± 13.93. The study revealed a significant positive relationship between spiritual health, resilience, and compassionate care in nurses (P < 0.05). Consequently, enhancing spiritual health and resilience scores positively influenced the compassionate care, and vice versa. CONCLUSION: To summarize a significant association exists between nurses' spiritual health, resilience, and their ability to provide compassionate care. It is recommended that educational programs are developed and implemented to enhance and maintain the spiritual health, compassionate care, and resilience of nurses, ultimately improving patient care.